Pravopisna obravnava imen znamk in industrijskih izdelkov ter posledice spreminjanja njihovih lastnoimenskih funkcij - Dobrovoljc, Helena (Jezik in slovstvo, 2009)
The article presents a linguistic treatment of brand names and the names of industrial products as groups of concrete proper names. Through changes at various levels of linguistic analysis, the process of the modification of the proper name function of brand names to various degrees is demonstrated, including its transition to a common name. Alongside the emergence of generic names from brand names there is a presentation of the treatment of these names in dictionaries from the second half of the 20th century, with an emphasis on providing an outline of the deficiencies of the actual codification. For the example of Teflon, an outline is provided of the difficulties arising from the contradiction between legislation and marketing principles, as well as linguistic principles.
Keywords: generična imena; hrematonimi; knjižna norma; onomastics; onomastika; orthography; pravopis; Slovene; slovenščina; stvarna imena